The Implementation of the Mind Mapping Model in Teaching Anecdote Text Writing among Grade X Vocational High School Students in the 2024-2025 Academic Year - Latifah, Siti Umi (Transpublika Publisher, 2025)
During the 2024-2025 academic year, Grade X of SMK NU Sukagumiwang students showed poor writing performance when composing anecdote texts, mainly due to their lack of interest in writing. To improve this situation, a study implemented the mind mapping model as a teaching strategy to enhance the students' ability to write anecdotes effectively. The study was aimed to assess the impact of the mind mapping model on Grade X students’ anecdote writing skills at SMK NU Sukagumiwang during the 2024–2025 academic year and to examine their level of engagement with this learning approach. This study uses a nonequivalent control group design experimental model. The research population is all grade X students of SMK NU Sukagumiwang Academic Year 2024/2025. The study applied a saturated sampling technique, assigning Class X TKJ with 20 students as the experimental group and Class X TKRO with 20 students as the control group. Research instruments included written tests and observation sheets. Statistical evaluation via the independent samples t-test yielded a t-statistic of 15.962, surpassing the t-table value of 1.686. This outcome confirms that the null hypothesis (H₀) is rejected and the alternative hypothesis (H₁) is accepted. Accordingly, the results demonstrate that the implementation of the mind mapping model effectively supports the development of anecdote writing skills among grade X students. As such, it is proven that the application of the mind mapping model can increase student activeness in the learning process of anecdote texts for grade X students of SMK NU Sukagumiwang Academic Year 2024/2025.